PENERAPAN ALGORITMA K-MEANS UNTUK CLUSTERING PENENTUAN JURUSAN BAHASA MANDARIN GERMAN DAN PRANCIS - Ardi Mardiana (PROCEEDING STIMA)
Grouping language department based on academic data using clustering techniques and create applications then analyze the results that are expected to provide the information concerned. K-Means algorithm is a clustering algorithm technique that starts with a random selection of K, which is the number of clusters to be formed from the data to be in clusters, namely student test scores when entering the majors language. System created to show the results of student academic data clustering, ie the pattern of student achievement lusternya remain, down and up, and can be seen from the data value of the test results. From the results of the case study can be obtained information of students who remain in clusters such as early admission, students who ride down clusters and clusters of students.Keywords : clustering, Algoritma K-Means.